AICCRA Zambia GESI Report 2025 - Mapedza, Everisto; Chakona, G.; Gbegbelegbe, Sika; Huyer, Sophia; Mudege, N.N.; Nortje, Karen; Makungwe, Mirriam; Jacobs-Mata, Inga; Mutenje, Munyaradzi; Gondwe, T. (2025)
The objective of this report is to review how households and women and men differentially access and use climate information services as mechanisms for risk management in the context of perceived climate change and climate variability, based on a study conducted in Zambia under the Accelerating Impacts of CGIAR Climate Research for Africa Project.